Pengembangan Handout Materi Sistem Koloid Berbasis Guided Note Taking untuk Meningkatkan Hasil Belajar dan Respon Siswa Kelas XI SMA - Sri Adelila Sari; Sulistia Ningsih Putri (JIPI (Jurnal IPA dan Pembelajaran IPA), 2020)
One reason for the low student learning outcomes is the inactivity of students in making notes independently. This study was aimed to develop (HGNT) on colloidal system material. The research method used was research and development (RD) with the 4D model, namely: (i) Define, (ii) Design, (iii) Development, and (iv) Disseminate. The research instrument used to assess the feasibility of the HGNT that has been developed was a validation sheet, while in the dissemination stage, learning outcomes and student responses were measured using an objective test and questionnaire. The study was conducted at Budisatrya Private High School Medan in class XI IPA 1. The results showed that the developed HGNT was obtained very decent criteria. In addition, student learning outcomes were found to be improved and student responses to HGNT showed a positive category. Based on the results of this study, it can be concluded that the HGNT which has been developed was very feasible to use in learning of the colloidal system material, and student learning could be success with a very positive responses